ACE2/ADAM17/TMPRSS2 Interplay May Be the Main Risk Factor for COVID-19 - Zipeto, Donato; Palmeira, Julys da Fonseca; Argañaraz, Gustavo A.; Argañaraz, Enrique R. (Frontiers in Immunology, 2020)
The Coronavirus Disease 2019 (COVID-19) has already caused hundreds of thousands of deaths worldwide in a few months. Cardiovascular disease, hypertension, diabetes and chronic lung disease have been identified as the main COVID-19 comorbidities. Moreover, despite similar infection rates between men and women, the most severe course of the disease is higher in elderly and co-morbid male patients. Therefore, the occurrence of specific comorbidities associated with renin–angiotensin system (RAS) imbalance mediated by the interaction between angiotensin-converting enzyme 2 (ACE2) and desintegrin and metalloproteinase domain 17 (ADAM17), along with specific genetic factors mainly associated with type II transmembrane serine protease (TMPRSS2) expression, could be decisive for the clinical outcome of COVID-19. Indeed, the exacerbated ADAM17 – mediated ACE2, TNF-α and IL-6R secretion emerges as a possible underlying mechanism for the acute inflammatory immune response and the activation of the coagulation cascade. Therefore, in this review, we focus on the main pathophysiological aspects of ACE2, ADAM17 and TMPRSS2 host proteins in COVID-19. Additionally, we discuss a possible mechanism to explain the deleterious effect of ADAM17 and TMPRSS2 over-activation in the COVID-19 outcome.